2005
DOI: 10.1177/13670069050090020601
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual early functional-lexical mixing and the activation of formal features

Abstract: We have argued that the grammatical features spell-out hypothesis (GFSH) (Liceras, Spradlin, Perales, Fernández, & Álvarez, 2003; Spradlin, Liceras & Fernández, 2003a) accounts for the functional-lexical mixing patterns that prevail in the case of Determiner Phrases produced by bilingual (English-Spanish) children. This hypothesis (Liceras, 2002; Spradlin, Liceras & Fernández, 2003b) states that in the process of activating the features of the two grammars, the child, who will rely on the two lexic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 35 publications
3
45
0
3
Order By: Relevance
“…In fact, the difference between their mean ratings for analogical criterion versus other agreement is almost 1.1 (out of 4) for both Adjectival Predicates and DPs, which is a much larger difference in the means than with other significant effects in the data. This finding is not surprising given the significant body of research that has consistently shown that Spanish-dominant bilinguals follow the analogical criterion, both in experimental (Liceras, Fernández Fuertes, Perales, Pérez-Tattam & Spradlin, 2008;Liceras, 2013;Valenzuela, Faure, Ramírez Trujillo, Barski, Pangtay, Diez, 2012) and spontaneous data (Liceras et al, 2005).…”
Section: Gender Use Strategiesmentioning
confidence: 83%
See 2 more Smart Citations
“…In fact, the difference between their mean ratings for analogical criterion versus other agreement is almost 1.1 (out of 4) for both Adjectival Predicates and DPs, which is a much larger difference in the means than with other significant effects in the data. This finding is not surprising given the significant body of research that has consistently shown that Spanish-dominant bilinguals follow the analogical criterion, both in experimental (Liceras, Fernández Fuertes, Perales, Pérez-Tattam & Spradlin, 2008;Liceras, 2013;Valenzuela, Faure, Ramírez Trujillo, Barski, Pangtay, Diez, 2012) and spontaneous data (Liceras et al, 2005).…”
Section: Gender Use Strategiesmentioning
confidence: 83%
“…(14) The preference for the analogical criterion in code-switching has also been shown in spontaneous data and is not limited to Spanish-dominant bilinguals. Simultaneous Spanish-English bilingual adults in Gibraltar produced significantly more switched Spanish-English DPs that adhere to the analogical criterion (p<.05) than DPs that do not (Liceras, Spradlin & Fernández-Fuertes, 2005). In addition, simultaneous French-German bilingual children displayed a preference for the analogical criterion in their production of French-German switched DPs (Radford et al, 2007).…”
Section: Spanish Dominant Spanish-english Bilingualsmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been reported that in the speech of Spanish/English bilinguals, Spanish determiners with English nouns (el book) are preferred over English determiners followed by Spanish nouns (the libro) (e.g. Liceras et al, 2008;Liceras, Spradlin, & Fernández-Fuertes, 2005;Moro Quintanilla, 2014;Valdés Kroff, 2016). These findings were argued to support a generativist view of feature spell-out where the language with the richest array of 'uninterpretable phi features' provides the surface realization of the functional category (Liceras et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Liceras et al, 2008;Liceras, Spradlin, & Fernández-Fuertes, 2005;Moro Quintanilla, 2014;Valdés Kroff, 2016). These findings were argued to support a generativist view of feature spell-out where the language with the richest array of 'uninterpretable phi features' provides the surface realization of the functional category (Liceras et al, 2005). This means that since the Spanish determiner carries two uninterpretable features (gender and number), while English has no gender, the Spanish determiner will be preferred in mixed nominal constructions.…”
Section: Introductionmentioning
confidence: 99%